Theoretical Linguistics with Clinical Reach: Two Case Studies in Morphological Development in Children with Hearing Loss - Hammer, Annemiek; Coene, Martine (Nordlyd, 2026)
This paper examines how theoretical linguistics and clinical research can inform one another through the study of language acquisition in children with hearing loss. It focuses on how perceptual constraints, such as reduced auditory input, shape the development of grammatical systems. The first case study investigates Dutch-speaking children with cochlear implants and their acquisition of past tense morphology. It compares the single-route model (a frequency-driven learning mechanism) and the dual-route model (a rule-based and memory-based system). Data from spontaneous speech and elicited production show that these children lag behind their hearing peers and display patterns not fully explained by either model. This suggests the need for approaches that integrate perceptual and morphosyntactic factors. The second case study explores determiner acquisition at the prosody–morphology interface. While typically developing children use prosodic cues to acquire indefinite articles, children with cochlear implants show a reversed pattern, producing definite articles earlier due to limited access to pitch cues. Together, the findings demonstrate that combining theoretical and clinical perspectives improves our understanding of grammar and supports more effective assessment and intervention strategies.